THE STATE BORDER DOCUMENTATION POLICY AND ITS IMPLEMENTATION - Altangerel Dalantai; Ganbold Tsagaan (International Journal of Innovative Technologies in Social Science, 2024)
The international community considers the border policy to be a crucial aspect of the country’s security and political strategy. The resolution of the state border issue has been in accordance with agreements, domestic laws, programs, and projects related to Mongolia’s international border. Therefore, the Mongolian government developed and approved the document "The basis of the Mongolian government’s border policy" in 2002 to establish a legal framework for coordinating state border activities, addressing related issues, and ensuring border protection. This document is based on the provisions of the Constitution, National Security and foreign policy concepts, and aims to evaluate the implementation of laws and international agreements while optimizing the legal environment. The document remains in force since its approval by the National Assembly in 2002. This supporting document outlines an ideological system that upholds the state’s independence, sovereignty, territorial integrity, and the inviolability of its borders. It also includes mechanisms for ensuring state border security, as well as the goals, objectives, principles, and main directions for its implementation. This document has been crucial in maintaining the continuity of government policy. In an era of increasing complexity in the global and regional security landscape, countries are focusing on safeguarding border security, addressing potential threats and risks, and maintaining national borders and territorial integrity. This underscores the significance of emphasizing unity, shared interests, and collective security over individual national interests and security. From ancient times (Great Mongolia) to the present day, Mongolia has consistently prioritized its border security and has implemented various policies and activities to safeguard the integrity of its borders. There has always been a requirement to create policy documents for border protection and enhance legal capabilities to safeguard the integrity of the state border, as well as to coordinate and oversee national border protection efforts based on societal needs, aims, and objectives. In light of Mongolia’s development policy and legal reform, the state military and institutions with special functions are undergoing reform. A series of state policy and legal documents have been updated and approved, establishing a legal framework. Consequently, there is a pressing need to review the government’s border policy, which has remained unchanged for two decades.